JUMPA Vol.3 No.2 Juni 2016 ANALISIS PENGARUH SERVICE QUALITY DAN EXPERIENTIAL MARKETING TERHADAP BRAND IMAGE COMMUTER: ANALISIS PENGARUH SERVICE QUALITY DAN EXPERIENTIAL MARKETING TERHADAP BRAND IMAGE COMMUTER - Haris Prahara Universitas Katolik Indonesia Atma Jaya, Jakarta; Yasintha Soelasih Universitas Katolik Indonesia Atma Jaya, Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
Nowadays service quality and experiential marketing is an important aspect that should be implemented by the company to enhance brand image and customer satisfaction. Commuters are mass transportation in Jabodetabek widely used for mobility. However, commuters still have a lot of weaknesses. The data used are primary data using questionnaires with closed scale. Questionnaires were distributed to 230 respondents who were commuter service users.Questionnaires using simple random sampling method. Data processed by Structural Equation Model (SEM) with LISREL 8.7. Experiential marketing results showed positive effect on the brand image of commuting, while variable service quality have no effect on the brand image of commuters.